PS-BPC09-5: THE RELATIONSHIP BETWEEN CHANGES IN EXERCISE HABITS, PHYSICAL FUNCTION, AND PSYCHOLOGICAL STATUS IN OLDER PATIENTS WITH HYPERTENSION. (January 2023) - Yasunobe, Yukiko; Akasaka, Hiroshi; Yamamoto, Kouichi; Onishi, Yuri; Minami, Tomohiro; Yoshida, Shino; Rakugi, Hiromi
Abstract : Objective: Self-restraint from activities due to the COVID-19 pandemic has limited the range of activities and interpersonal relationships for older persons. Moreover, prolonged restraint has been reported to increase the risk of frailty and sarcopenia. Therefore, we examined the effects of changes in exercise habits on physical function and psychological status of older patients with hypertension throughout their self-restraint lifestyle from 2020 to 2022 in the 1-year follow-up study. Design and Methods: Participants were patients with hypertension aged 65 years or older attending outpatient clinics at our institution who could obtain information on exercise habits, history of falls, comprehensive geriatric assessment, and muscle strength. We conducted the same survey in the first year and one year later. The subjects were classified into four groups by combining their exercise habits in the first year with or without one year later. That is Group A: with exercise habits at both times of the survey; Group B: with exercise habits in the first year and without exercise habits one year later; Group C: without exercise habits in the first year and with exercise habits one year later; and Group D: without exercise habits at both times of the survey. Written consent forms were obtained from all participants. Our institutional review board approved the study protocol. Results: The study participants were 183 patients (Group A: 119, Group B: 26, Group C: 17, Group D: 21). The age of the participants was 76.1 ± 5.5 years, 82 (44.8%) were male, and the duration of hypertension was 18.4 ± 11.5 years. Changes in exercise habits were not associated with physical function, history of falls, and comprehensive geriatric assessment at one year. However, when the results were examined separately for men and women, the geriatric depression scale was significantly higher in women in Group B (Dunnett test, p = 0.0094) than in Group A, suggesting that the tendency toward depression had progressed. Group B women also had more falls one year later (chi-square 12.04, p = 0.0072). Conclusions: In a 1-year follow-up study during the COVID-19 pandemic, a relatively high proportion of older patients with hypertension attending our hospital maintained their exercise habits, but 14% of cases lost their exercise habits. Only women showed the development of depression and increased risk of falls when exercise habits were lost. Women were more susceptible to the effects of environmental changes than men in older patients with hypertension.